2011
DOI: 10.1177/0255761410372725
|View full text |Cite
|
Sign up to set email alerts
|

Focus of attention to melody or harmony and perception of music tension: An exploratory study

Abstract: This project represents an initial investigation into utilizing the two-dimensional Continuous Response Digital Interface (CRDI) to track listener perceptions related to the possible relationships between focus of attention to musical elements and perceived musical tension. The two-dimensional CRDI software creates an environment in which the listener can track their perceptions on two planes simultaneously. Volunteer undergraduate and graduate music majors (N = 60) listened to Mozart's Variations (12) for Pia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
(35 reference statements)
1
7
0
1
Order By: Relevance
“…These negative correlations may have resulted from the slow rate of harmonic change of the Mendelssohn piece, which rendered the harmonic reduction rather uninteresting to listen to, thus accounting for the relatively flat tension profile of the harmony version and its slight downward trend. The larger contribution of harmony on experienced tension observed for the Mozart piece is also in concordance with results by Williams, Fredrickson, and Atkinson (2011), who showed that focusing more on harmony of a Mozart piece was related to higher tension ratings as compared with attending more to the melody, which indicates a higher importance of harmony in comparison to melody for inducing an experience of tension in Mozart pieces.…”
Section: Discussionsupporting
confidence: 89%
“…These negative correlations may have resulted from the slow rate of harmonic change of the Mendelssohn piece, which rendered the harmonic reduction rather uninteresting to listen to, thus accounting for the relatively flat tension profile of the harmony version and its slight downward trend. The larger contribution of harmony on experienced tension observed for the Mozart piece is also in concordance with results by Williams, Fredrickson, and Atkinson (2011), who showed that focusing more on harmony of a Mozart piece was related to higher tension ratings as compared with attending more to the melody, which indicates a higher importance of harmony in comparison to melody for inducing an experience of tension in Mozart pieces.…”
Section: Discussionsupporting
confidence: 89%
“…Continuous measurements, in which participants provide real-time feedback through a dial, slider, or software, have been used extensively in studies of music perception in relation to musical stimuli as they change over time, including listeners' genre preferences (Brittin and Sheldon, 1995 ), perception of loudness (Geringer, 1995 ), focus of attention (Madsen and Geringer, 1999 ; Williams et al, 2011 ), perception of musical intensity (Brittin and Duke, 1997 ), perceived tension (Madsen, 1998 ; Vines et al, 2006 ; Williams et al, 2011 ), perceived expressivity (Silveira and Diaz, 2014 ), and emotional responses (Madsen, 1998 ; Schubert, 1999 , 2004 ; Nagel et al, 2007 ; Egermann et al, 2009 ). Such measures, however, have had relatively limited use in studies of performance evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Participant comments in this study described how the kinesthetic act of moving the dial prompted focus of attention during the process of decision-making process. The CRDI dial has been used as a device to monitor focus of attention on music elements (e.g., harmony, melody) while listening to a piece of music (Williams, Fredrickson, & Atkinson, 2011). Findings from the current study suggest that the CRDI dial could be used as a pedagogical tool, enhancing focus of attention during a cognitive process of making complex and sometimes daunting decisions.…”
Section: Discussionmentioning
confidence: 99%